Highly Stable Single‐Atom Modified MXenes as Cathode‐Active Bifunctional Catalysts in Li–CO2 Battery. (30th September 2022) - Shi, Yu; Wei, Bo; Legut, Dominik; Du, Shiyu; Francisco, Joseph S.; Zhang, Ruifeng
Abstract: The exploration of cathode catalysts with low overpotentials for the carbon dioxide reduction reaction (CRR) and carbon dioxide evolution reaction (CER) is essential for Li–CO2 batteries. MXenes have been suggested as potential candidates owing to their high electrical conductivity and effective CO2 activation performance. Herein, the stability and bifunctional CRR/CER catalytic activities of bare MXene (M2 C), oxygen‐functionalized MXene (M2 CO2 ), and single‐atom (SA) modified M2 CO2 are systemically investigated. Among bare MXenes, Mo2 C exhibits the best catalytic activity, comparable to that of carbon nanotubes, whereas oxygen‐functionalized MXene has poor activity. Notably, introducing an SA on the surface of oxygen‐functionalized MXene decreases the overpotential by 12.2%–68.1%, which can even outperform graphene catalysts, suggesting their potential as bifunctional cathode catalysts in Li–CO2 batteries. This high activity is appropriate reactivity in origin, as highlighted by the volcano‐type relationship between the Gibbs free energy and the overpotential for key steps. The descriptor ξ, which is related to adsorption behavior, is effective in determining bifunctional catalytic activity, which depends on the ability of SA electrons to fill antibonding orbitals and SA–oxygen/carbon bonding. This study not only identifies promising MXene‐based bifunctional CRR/CER catalysts but also provides a rational design rule for SA modified catalysts. Abstract : The bifunctional carbon dioxide reduction/evolution reaction properties of various thermodynamically stable MXenes are explored. Mo2 C performs best among bare MXenes, but surface O groups drastically decrease the activity. Transition metal screening for single‐atom modification of Mo2 CO2 catalysts reveals Mn, Fe, Zn, Cd, and Ag as optimal candidates by modulating the adsorption ability for key reactants to improved catalytic activity.